Contributions of twisting techniques used in backward somersaults with one twist - Yeadon, M. R.; Kerwin, D. G. (Journal of Applied Biomechanics, 1999)
At the 1996 Atlanta Olympic Games, 18 single somersaults with one twist in the women`s compulsory floor exercises were recorded using two video cameras. An 11 segment computer simulation model was used to analyze the twisting techniques used. It was found mat counter-rotation techniques accounted for less than one third of the twist for all gymnasts, indicating that the production of twist was mainly a consequence of the angular momentum and a non-zero tilt angle. Contributions to the tilt angle reached at the mid-twist position were used as measures of the twisting potential of various techniques. Contact techniques accounted for 30% of the tilt produced, the remainder being produced using aerial techniques, which primarily comprised a symmetrical lowering of the arms together with minor contributions from asymmetrical arm and hip movements. There was no evidence of a difference in technique between the highest and lowest scoring competitors.